2014
DOI: 10.1074/jbc.m113.509331
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenic Protein (BMP) Signaling Up-regulates Neutral Sphingomyelinase 2 to Suppress Chondrocyte Maturation via the Akt Protein Signaling Pathway as a Negative Feedback Mechanism

Abstract: Background: It is not clear how BMP-induced chondrocyte maturation is cell-autonomously terminated. Results: BMP-2 induced the ceramide-generating enzyme neutral sphingomyelinase 2 (nSMase2) in chondrocytes, whereas silencing of nSMase2 enhanced maturation in an Akt signaling-dependent manner. Conclusion: nSMase2 signaling regulates BMP-induced chondrocyte maturation as a negative feedback mechanism. Significance: This study elucidated the novel link between BMP and lipid signaling in chondrogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 70 publications
1
39
0
Order By: Relevance
“…In agreement with the strong Smpd3 expression reported in both chondrocytes and osteoblasts, SMPD3 deficiency affects the initiation of mineralization in both cartilage and bone (4,26). It was shown earlier that bone morphogenetic protein (BMP) signaling and chondro-osteogenic transcription factor RUNX2 might be involved in the regulation of Smpd3 expression (24,27). Furthermore, SMPD3 has been shown to act as a negative regulator of chondrocyte hypertrophy in the developing growth plates (24,27).…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In agreement with the strong Smpd3 expression reported in both chondrocytes and osteoblasts, SMPD3 deficiency affects the initiation of mineralization in both cartilage and bone (4,26). It was shown earlier that bone morphogenetic protein (BMP) signaling and chondro-osteogenic transcription factor RUNX2 might be involved in the regulation of Smpd3 expression (24,27). Furthermore, SMPD3 has been shown to act as a negative regulator of chondrocyte hypertrophy in the developing growth plates (24,27).…”
Section: Discussionsupporting
confidence: 58%
“…We decided to use this proximal Acan promoter fragment in our transgene because of the similar expression patterns of both Acan and Smpd3 during growth plate development (27,31). In fro/fro; Acan-Smpd3 embryos, although growth plate cartilage mineralization was largely normalized, we did not observe a full correction of the skeletal deformities.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Runx2 was highly expressed in hypertrophic chondrocytes and osteoblasts [19,27,28], and C/EBPb could enhance Runx2 activity in ossification [21]. The Runx2-dependent expression of sphingomyelin phosphodiesterase 3 (Smpd3) was increased by Bone morphogenic protein 2 (BMP-2) stimulation, and Smpd3 knockdown decreased the apoptosis of terminally matured ATDC5 chondrocytes [33]. Furthermore, Runx2 regulated the differentiation of MSCs as the target of miRNAs [22,23], such as miR-199a ⁄ , a BMP2-responsive miRNA that regulates chondrogenesis via the direct targeting of Smad1 in murine MSCs [35].…”
Section: Discussionmentioning
confidence: 99%
“…Runx2 is an important regulator in chondrogenic differentiation and endochondral ossification, and it was shown that Runx2 regulated endochondral ossification by controlling chondrocyte proliferation and differentiation [1,27,[32][33][34]. Runx2 was highly expressed in hypertrophic chondrocytes and osteoblasts [19,27,28], and C/EBPb could enhance Runx2 activity in ossification [21].…”
Section: Discussionmentioning
confidence: 99%